The Role of African States in Implementing International Legal Mechanisms for Addressing Armed Conflicts and Ensuring Accountability - Caroline, Adeke; Enoch, Otim (International Journal of Humanities and Education Development (IJHED), 2024)
This paper explores the role of African states in adopting international legal mechanisms to address armed conflicts and ensure accountability. This article also argues that the recent efforts of African states in this respect represent a new and promising direction, despite the limitations and difficulties in making the international legal mechanisms work effectively for the benefit of the people in certain African states. This article further elucidates the nature and causes of recent armed conflicts in Africa and by evaluating these as a catalyst for change in the approach of African states to the international legal mechanisms in question. It provides an overview of the key international legal mechanisms and measures taken by African states to address armed conflicts and ensure accountability and will then discuss the involvement of African states in the making of these mechanisms. Finally, the paper will quote several recent examples of the utilization of international legal mechanisms by African states to address armed conflicts and ensure accountability and will assess the results.